Impact of support structure on surface roughness and mechanical properties of PLA 3D printed parts by FDM - Intissar Antar; Khalid Zarbane; Mohamed El Oumami; Zitouni Beidouri (Incertitudes et Fiabilité des Systèmes Multiphysiques)
This study investigates the effect of support infill angle and its density, transverse at 90°, inclined at 45°, axial direction at 0° and crossed filament by (0°/90°), (45°/-45°) and (0°/45°) on surface quality and mechanical properties using three different strategies. The surface roughness and flexural properties of the specimens are analysed and compared as well as the material waste and printing time. According to results of this study, the variations in the support infill angle resulted in diverse flexural strength and surface quality.